A comprehensive investigation into the structure-property relationship of wax and how it influences the properties of hot melt adhesives. (June 2020) - Robertson, Divann; van Reenen, Albert; Duveskog, Heidi
Abstract: A detailed study was conducted on seven different waxes used in hot melt adhesive formulations together with conventional resins and tackifiers, to characterize the waxes and investigate the effects of wax structure and morphology on the thermal behaviour and basic properties of the resultant hot melt adhesive formulations (HMAs). The waxes selected included representatives of each of the following types: Fischer-Tropsch wax (FT), fully refined paraffin wax (FRP), by-product polyethylene wax (BPPE), microcrystalline wax (microwax), alpha-olefin wax (AO), carnauba wax and first intention polyethylene wax (FIPE). Fourier-transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), high temperature size exclusion chromatography (HT-SEC), nuclear magnetic resonance spectroscopy (NMR) and confocal laser scanning microscopy (CLSM) were used as analytical tools to characterize the waxes. Molecular chain architecture as determined by solution 13 C NMR highlighted the superior chain linearity of FT wax. Methyl, ethyl and butyl short chain branching were detected in other waxes. Solid-state 13 C CP-MAS NMR provided information on the semi-crystalline nature of the waxes. FIPE, AO and Microwax showed significant structural mobility at room temperature as observed by 1 H Wideline NMR and was attributed to chain branching and mobile crystalline domains respectively. This was supported by CLSM micrographs. All waxes enhanced crystallinity in both metallocene catalysed polyethylene (mPE) and ethylene-vinyl acetate (EVA) based HMAs. This was confirmed by the characteristic splitting in FTIR bands and increased DSC enthalpies observed for the HMA relative to the neat polymers. Of the formulations containing high melting waxes, FT wax resulted in HMAs with narrower crystallization profiles, an important factor in determining HMA set times. HMA viscosities were found to be dependent on the molecular weight of the wax while the HMA melting temperatures and enthalpies were more dependent on the crystalline morphology of the waxes.